2004
DOI: 10.1093/heapro/dah206
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of smoking behaviors among medical and other college students in China

Abstract: A survey of students' smoking in China (n = 1896), comparing medical students with college students in non-medical majors, was carried out to determine whether a medical education has a preventive effect on smoking uptake. The survey, sampling students from 12 universities in three cities, found no significant differences between medical and non-medical students in smoking prevalence (40.7% versus 45.1% for males, 4.4% versus 6.0% for females), in 'ever smoked' groups, in 'ever smoked 100 cigarettes' groups or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
31
5
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 14 publications
8
31
5
5
Order By: Relevance
“…Similar high prevalence rates were also found among university students in previous studies in Bangladesh (Kamal et al, 2011), Kyrgyzstan (Agaku et al, 2013), Tunisia (Khefacha Aissa et al, 2014), Turkey (Onal et al, 2002) and in national adult data in Russia (WHO, 2014b). Compared to a previous study among university students in Cameroon (Mbatchou Ngahane et al, 2013), this study found a much higher prevalence of current tobacco use, and this study found a lower prevalence of tobacco use in China than in a previous study (Zhu et al, 2004). Among the different study regions, Near East and Central Asian countries had the highest and the Southeast Asian region countries the lowest prevalence of tobacco use, which confirms findings from the Global Youth Tobacco Surve in these regions (Warren et al, 2006).…”
Section: Discussionsupporting
confidence: 78%
“…Similar high prevalence rates were also found among university students in previous studies in Bangladesh (Kamal et al, 2011), Kyrgyzstan (Agaku et al, 2013), Tunisia (Khefacha Aissa et al, 2014), Turkey (Onal et al, 2002) and in national adult data in Russia (WHO, 2014b). Compared to a previous study among university students in Cameroon (Mbatchou Ngahane et al, 2013), this study found a much higher prevalence of current tobacco use, and this study found a lower prevalence of tobacco use in China than in a previous study (Zhu et al, 2004). Among the different study regions, Near East and Central Asian countries had the highest and the Southeast Asian region countries the lowest prevalence of tobacco use, which confirms findings from the Global Youth Tobacco Surve in these regions (Warren et al, 2006).…”
Section: Discussionsupporting
confidence: 78%
“…This prevalence is lower than other studies conducted in Malaysia found that 26.6% (Hashami et al, 1994) and 29.9% (Al-Naggar et al, 2011) among students. The prevalence of smoking in this study is lower compared too ther studies conducted in China 45.1% (Zhu et al, 2004), European countries Croatia 36.6%, Lithuania 27.6% and Czech Republic 21.6% (Warren et al, 2008) and Turkey 20.4% (Golbasi et al, 2011), but the present study prevalence is higher than Hong Kong 0.7 % (Lam et al, 2009). The major reason for lesser prevalence of smoking cigarette among students population is due to social custom, family restriction and cultural issues in Malaysia.…”
Section: Discussioncontrasting
confidence: 73%
“…5,6,9,2,9 It was found that non medical students smoked more than medical students and this was supported by the study conducted at 12 universities in China. 20 The study conducted at Rawalpindi Pakistan revealed the similar results. 21 It may be due to medical education that has exposed to preventive effect on smoking.…”
Section: Discussionmentioning
confidence: 58%